1990
DOI: 10.1111/j.1365-2621.1990.tb06753.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Some Physical and Chemical Changes in Vacuum‐Packaged Beef Steaks Treated with Combinations of Potassium Sorbate, Phosphate, Sodium Chloride and Sodium acetate

Abstract: Fresh rib eye steaks were examined for microbiological, lipid oxidation, pH, color and weight changes after immersion in water or in aqueous solutions of a phosphate blend and of a mixture of potassium sorbate, phosphates, sodium chloride and sodium acetate and subsequent vacuum packaging. Keeping characteristics of steaks were monitored during 12-wk storage at 2-4"C. Mesophilic, psychrotrophic, anaerobic and facultative anaerobic bacteria and lactobacilli were strongly inhibited (PcO.05) in steaks treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Other salts of organic acids such as NaA, NaC and NaP have been used to control microbial growth, preserve color, solubilize proteins and prevent mold growth (Vanderzant et al, 1983;Marth, 1989, 1992;Krueger and Fennema, 1989;Unda et al, 1990;Kim and Hearnsberger 1994;Wederquist et al, 1994;Kim et al, 1995). NaC at 0.23% also has been shown to inhibit toxin formation by Clostridium botulinum in processed cheese food (Karahadian et al, 1985).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other salts of organic acids such as NaA, NaC and NaP have been used to control microbial growth, preserve color, solubilize proteins and prevent mold growth (Vanderzant et al, 1983;Marth, 1989, 1992;Krueger and Fennema, 1989;Unda et al, 1990;Kim and Hearnsberger 1994;Wederquist et al, 1994;Kim et al, 1995). NaC at 0.23% also has been shown to inhibit toxin formation by Clostridium botulinum in processed cheese food (Karahadian et al, 1985).…”
Section: Introductionmentioning
confidence: 97%
“…Shelf life of uncured meat products has been increased by addition of nonmeat ingredients such as NaL (Maas et al, 1989;Brewer et al, 1991Brewer et al, , 1995Papadopoulos et al, 1991a, b;Miller and Acuff, 1994;Williams et al, 1995). Other salts of organic acids such as NaA, NaC and NaP have been used to control microbial growth, preserve color, solubilize proteins and prevent mold growth (Vanderzant et al, 1983;Marth, 1989, 1992;Krueger and Fennema, 1989;Unda et al, 1990;Kim and Hearnsberger 1994;Wederquist et al, 1994;Kim et al, 1995). NaC at 0.23% also has been shown to inhibit toxin formation by Clostridium botulinum in processed cheese food (Karahadian et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…However, Bechtel et al (11) reported that it had no effect on the total plate counts of frankfurters, when compared to a sodium chloride control. Sodium acetate extended the shelf-life of vacuum-packaged beefsteaks when used in combination with other additives (12). Sodium acetate was also effective in controlling L. monocytogenes in meat and broth (13).…”
Section: Introductionmentioning
confidence: 98%
“…Most of the study reported on the changes of soluble sarcoplasmic reticulum protein, including changes in activity and molecular mobility (Murphy and Marks, 2000;Unda. et al, 1990).…”
Section: Discussionmentioning
confidence: 98%